HUMAN RESOURSES CRISIS MANAGEMENT: A CONCEPTUAL APPROACH - E. Mitrofanova; I. Esaulova (Вестник университета, 2017)
Crises, which have become an integral part of modern social development, permeate the sphere of human resourses management, which requires a scientific justification for the specifics of their manifestation in the organization and the identification of negative consequences. The characteristics of the crises of efficiency, competence, motivation, culture and social and labor relations, as well as «personnel hunger» are identified. A cyclical model of the process of human resourses crisis management is presented, the content of the types of activity of the personnel service is disclosed at its stages. The principles of building an effective system of human resourses crisis management are formulated.